A new species of Temnocephala (Platyhelminthes) with an unusual pharynx, including an amendment of the diagnosis of the genus - de León, Rodrigo Ponce; Volonterio, Odile (Zootaxa, 2018)
Three species of Temnocephala have been reported on Aegla from Uruguay: Temnocephala axenos, Temnocephala mertoni and Temnocephala talicei. As part of a systematic review of the Uruguayan species of Temnocephala, a fourth species was found on Aegla platensis and Aegla uruguayana. This species, new for the genus, has the following diagnostic characters: Large temnocephalan; slightly curved penial stylet (225 µm in length) with a symmetrical introvert (27 long by 18 µm in diameter) that has at least 44 spine-like projections, each bearing 7 rows of internal spines; a seminal vesicle that opens sub-polarly into the contractile vesicle; a muscular vagina with a strong asymmetrical sphincter; preequatorial nephridiopores close to the internal borders of the elongate-oval excretory syncytia; a large pharynx with anterior and posterior sphincters of about the same diameter and a narrow pharyngeal lumen with nearly uniform width. To contemplate the characters of the pharynx, an amendment of the genus Temnocephala is given. The new species resembles Temnocephala cyanoglandula, which also has a very long, slightly curved penial stylet, but differs from it by having a shorter penial stylet, a lower number of rows of spines in the introvert, a larger, different type of pharynx, a smaller contractile vesicle and a larger sucker. The new species is carnivorous and feeds on whole preys, which are mainly annelids (Stratiodrilus) and other species of Temnocephala. The new species was found to be hyperparasitised by plerocercoid and nematode larvae, but hyperparasites were not found in the other sympatric species of Temnocephala. Based on the findings presented here, it is clear that detailed histological descriptions of the pharynx should be contemplated as part of the normal work in taxonomy of temnocephalans.